Relived vulnerabilities of palestinian refugees: governing through exclusion - Almustafa, Maissaa (2018)
The international refugee protection regime failed in protecting millions of refugees during the current Syrian conflict. However, for more than half a million Palestinian refugees who have resided in Syria since 1948, this failure has been persistent since such time as they were never protected by the international protection regime. These Palestinian refugees are now reliving the trauma of their statelessness through the current Syrian conflict. Their lack of protection reveals a complex layering of the failure of the legal framework of refugee protection. This case demonstrates the limits of an international protection regime that was initially formulated to address a Eurocentric set of concerns. This article links the current protection gaps for Palestinian refugees from Syria with the structural flaws of the international refugee protection regime. The article argues that the particular legal frameworks that were established to govern the statelessness of Palestinian refugees since 1948 have contributed in prolonging this unresolved crisis and pushed stateless Palestinians into a new cycle of displacement and victimization . - Reproduced.
Keywords: Exclusion; Refugees - Palestine; UNHCR; UNRWA